Occupying Inherited Land Rights Impllemented Without The Consent of The Heirs - Naila Nur Auliyah Azis; Ana Silviana (Universitas Batanghari Jambi, 2023)
Land rights can be transferred or transferred to other parties. The transfer of land rights means that the ownership of the land rights is transferred by law or by itself. However, in practice, there are many violations of the transfer of land rights without the consent of the heirs. This study will analyze the problem of the transfer of land rights whose object is the object of a land dispute in accordance with the case that occurred in the Supreme Court Decision Number 723 PK/PDT/2017. The purpose of this study is to find out, analyze, and describe: (1) whether the transfer of land rights without the consent of the heirs can be declared valid and has legal force; and (2) what are the legal consequences of the transfer of land rights without expert approval. The results of this study indicate that: (1) The acquisition of property rights to land can occur through inheritance from the heir to his legal heirs in accordance with what is stipulated in the UUPA; and (2) legal protection for heirs whose rights have been impaired on the transfer of rights to inherited land that are controlled and used without the consent of their heirs based on Article 1365 are against the law, so that they are given the right to file a lawsuit in order to defend their inheritance rights by proving that they are legal heirs.